ECONOMIC ANALYSIS OF COST AND RETURNS AMONG COOPERATIVE TOMATO FARMERS IN ODEDA LOCAL GOVERNMENT AREA OF OGUN-STATE, NIGERIA - Abbas, Ogundipe O.; Shittu, K. Adesina; Adeeko-Bakare, F. Adetutu (FUDMA JOURNAL OF SCIENCES, 2025)
The study examined econmics analysis of cost and returns among cooperative tomato farmers in Odeda local government area of Ogun-State, Nigeria. Data was gathered through a well-structured questionnaire administered to eighty (80) tomato farmers using a two-stage sampling technique. Both descriptive and inferential statistics were absorbed to analyzed the data. The result showed that majority of the respondents were male (90%), (68.7%) of them were educated and married (73.7%) while most of them were in their active years, with average family size of 4 persons with mean amount of ₦455,045.45 as monthly income.The calculated Rate of Return on investment (ROR), Profitability ratio (PR), Rate of returns on variable cost (RRVC) and Benefit-Cost ratio (B/C) were 35%, 0.59, 144.6% and 1.35 respectively. The findings further showed benefit-cost of 1.35, implying that for every ₦1.00 spent by the farmers on tomato production, 35 kobo was realised as profit, showing that the enterprise is profitable and economical since, benefit-cost ratio exceeded 1. Majority of farmers were predominantly rely on their personal savings, with minimal aid from cooperative societies.The study recommended that tomato farm Input such as fertilizers, seeds and others should be made available to the farmers at a subsidized rate and also try to provide credit facilities for the tomato farmers by government and non-government agencies. Timely and adequate training should be given to tomato farmers to acquire modern tomato production techniques. Tomato farmers should be educated on how to tackle constraints facing them.